التدابير التنفيذية التي يحق للدولة الساحلية اتخاذها في البحر الإقليمي - أحمد, بسام (Latakia University Journal - Economic and Legal Sciences Series, 2016)
استقر العرف على أن للدولة الساحلية سيادة تامة على بحرها الإقليمي وعلى قاعه وباطن قاعه وما يعلوه من طبقات الجو، كما أن من المسلم به أيضاً أن هذه السيادة مقيدة لمصلحة الجماعة الدولية بما يعرف باسم " حق المرور البريء "إن فعالية قواعد القانون الدولي المتعلقة بالبحر الإقليمي تتوقف على قدرتها في تحقيق التوازن بين مصلحة الدولة الساحلية في سيادتها على البحر الإقليمي وبين مصلحة الجماعة الدولية في الملاحة عبر هذا البحروهذا يرتبط بالتزام الدول بسَن التشريعات واللوائح واتخاذ الإجراءات التنفيذية المتوافقة مع القانون الدولي بما يضمن استقرار العلاقات الدولية في هذا الحيز الهام من البحارThe custom was settled that the coastal state had complete sovereignty on its regionalized sea, benthos, interiority of benthos and layers of atmosphere, taking for granted that this sovereignty was restricted by the international community interests which known as “the right of innocent passage”.The effectiveness of rules of international law, which was related to regionalized sea, depended on its ability to achieve balance between the interest of coastal state in its sovereignty on regionalized sea and the interest of international community in the navigation across the regionalized sea.In fact, this could be achieved when states were committed to enact legislations, measures and executive procedures which were compatible with international law which could led to the settlement of international relations in this part of the sea.